Inability of a negative faecal occult blood test to rule out intussusception in children. Issue 7 (26th June 2017) - Chin, Alvin; De Wit, Kerstin
Abstract : A short cut review was carried out to establish whether a negative faecal occult blood test was sufficiently sensitive to rule out a diagnosis of intussusception in children. 5 papers presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. It is concluded that a negative faecal occult blood test cannot reliably rule out the diagnosis of intussusception .